Digital Transformation and Blockchain Technology: A Viewpoint from Emerging Markets - Meria, Lista; Fabian, Stefanus; Victorianda; Mariyanti, Tatik (Blockchain Frontier Technology, 2024)
In the context of digital transformation, this paper provides a thorough analysis of the theoretical underpinnings and real-world applications of blockchain technology. Blockchain is a revolutionary technology that is improving security, transparency, and operational efficiency and is causing significant changes in a number of industries. This study evaluates the practical efficacy of blockchain concepts in supply chain management, healthcare, and finance by reviewing a large body of research on decentralization, cryptographic security, and consensus methods. The report also identifies important barriers to blockchain adoption, such as scalability constraints, regulatory barriers, and interoperability problems. Through an analysis of these challenges, the study offers insights into the obstacles that must be overcome in order to apply blockchain technology more widely. The paper demonstrates how blockchain technology is being used to propel digital transformation by fusing theoretical viewpoints with actual case studies. The study illustrates the useful advantages and potential of blockchain in building more transparent, safe, and effective systems through these case studies.